Interpersonal Rhetoric in Social Media Facebook - Agustinus, Jati Wahyono (Universitas Muhammadiyah Surakarta, 2017)
The research was conducted to describe the politeness in rhetoric social media communication on Facebook. In Facebook, many statements are made in which they frequently contain less decency, less respect for others, and even inappropriate expressions. The prevailing form of politeness used in the communication on social media, especially Facebook, was investigated. The Pragmatic theory of interpersonal rhetoric by using the principle of politeness that consists of six maxims, namely expression of tact, generosity, approbation, modesty, agreement, and sympathy, was employed in this study. These maxims have their respective roles and functions in oral and written communication. The purpose of this study was to describe the use of these six maxims in the communication on Facebook. The method was descriptive method by retrieving data obtained from Facebook, in the form of qualitative ones. Thirty conversations were selected. The collected data were documented in written form and analyzed by using the Pragmatic theory of modesty in interpersonal rhetoric. Based on the results of the analysis, the interpersonal rhetoric based on the principle of politeness is divided into six maxims. The most widely used expression is the expression of Agreement (40%), Sympathy (33.3%), and Approbation (10%).